Bayesian Binomial Contrast in the University Business Consulting Program - Rozo, Jairo Jamith Palacios; Ordóñez, Diego Alejandro López; Guerrero, Lugo Manuel Barbosa (Journal of Ecohumanism, 2024)
Significant progress has been made in the implementation of university business consulting programs as spaces for articulation between academia and the productive sector. However, there remains a need to better understand the qualitative characteristics and willingness of the beneficiary population toward the advisory services offered by these initiatives. The purpose of this study was to analyze the availability of microentrepreneurs to receive business consulting sessions on Saturdays, within the framework of the Business Consulting Project of the Bachelor in Business Administration program at the Faculty of Administration and Economics, Universidad Colegio Mayor de Cundinamarca. A total of 570 microentrepreneurs participated, completing a characterization instrument designed for this purpose. Through a Bayesian binomial contrast, the probability of acceptance of the proposed schedule was evaluated, considering gender as an explanatory variable within the inferential analysis. The results show a high posterior probability of availability, with marginal differences by gender, suggesting a generally favorable perception of the proposed schedule flexibility. Sequential analysis confirmed the stability of the model and the consistency of the empirical evidence. It is concluded that Bayesian inference is an effective decision-making tool in applied academic environments, as it enables the integration of prior and observed information into the planning processes of the consulting program.